The Effect of Using Powtoon Media on Elementary School Students' Motivation - Fanny Nelviandra; Leny Julia Lingga (MASI Mandiri Edukasi, 2026)
The integration of technology-based media into elementary education has the potential to enhance students’ motivation to learn, particularly in science subjects. This study aimed to examine the effect of Powtoon media on the learning motivation of elementary school students in Pekanbaru City. A quasi-experimental design with a non-equivalent control group was employed, involving 59 students divided into an experimental group (n = 30) and a control group (n = 29). Learning motivation was measured using a validated questionnaire administered before and after the intervention. Data were analyzed using normality and homogeneity tests, paired and independent samples t-tests, and N-gain calculations. Results indicated a significant increase in learning motivation in the experimental group, with mean scores rising from 59.03 to 84.63 and an N-gain of 0.60 (moderate to high). A significant difference was also observed between the experimental and control groups (t = 5.625; p < 0.05). These findings suggest that Powtoon media is an effective digital learning tool for enhancing elementary students’ motivation in science education. The study contributes to educational practice by demonstrating that animation-based media can create engaging, interactive, and student-centered learning environments, particularly in schools with limited technological resources.